Heart failure in type 2 diabetes: current perspectives on screening, diagnosis and management - Antonio Ceriello; Doina Catrinoiu; Chanchal Chandramouli; Francesco Cosentino; Annique Cornelia Dombrowsky; Baruch Itzhak; Nebojsa Malić Lalic; Francesco Prattichizzo; Oliver Schnell; Petar M. Seferović; Paul Valensi; Eberhard Standl; et al. (Cardiovascular Diabetology, 2021)
Abstract Type 2 diabetes is one of the most relevant risk factors for heart failure, the prevalence of which is increasing worldwide. The aim of the review is to highlight the current perspectives of the pathophysiology of heart failure as it pertains to type 2 diabetes. This review summarizes the proposed mechanistic bases, explaining the myocardial damage induced by diabetes-related stressors and other risk factors, i.e., cardiomyopathy in type 2 diabetes. We highlight the complex pathology of individuals with type 2 diabetes, including the relationship with chronic kidney disease, metabolic alterations, and heart failure. We also discuss the current criteria used for heart failure diagnosis and the gold standard screening tools for individuals with type 2 diabetes. Currently approved pharmacological therapies with primary use in type 2 diabetes and heart failure, and the treatment-guiding role of NT-proBNP are also presented. Finally, the influence of the presence of type 2 diabetes as well as heart failure on COVID-19 severity is briefly discussed.